Respostas

A melhor resposta!
2014-07-24T19:49:34-03:00
X²+x=12                  
                                                                          x = -b ± √Δ / 2a     
                                             Δ = b² - 4ac                 -1± √49 / 2X1
                                           Δ= (1)²-4X1X(-12)                  x¹= -1+9/2      x²= -1-9/2
a=1                                      Δ=  1 + 48=49                      x¹= 8/2           x²= -10/2
b=1                                                                             x¹= 4              x²= -5
c=-12

1 5 1